Analisis Hubungan Preferensi Mata Kuliah dengan Motivasi Belajar Mahasiswa Akuntansi Syariah UIN Bandung Tahun 2023 (Jurnal Kendali Akuntansi, 2025)
This study investigates the relationship between the level of fourth-semester students' interest in a course and their learning drive. The research focus is on students from the Sharia Accounting Study Program at UIN Sunan Gunung Djati Bandung, batch of 2023. We assume that interest in a course can influence learning enthusiasm, which subsequently impacts the quality of learning and academic achievement. A quantitative approach, specifically a correlational design, was applied in this research. Questionnaires were distributed to fourth-semester students to collect data, which were then analyzed using the Pearson correlation test. The research results indicate a substantial relationship between students' interest in a course and their learning motivation; an increase in interest is directly proportional to an increase in motivation.